Aligning Business Engineering Education with Contemporary Industry Requirements - Gruenewald, Hazel (School of Business and Management Institut Teknologi Bandung, 2019)
Abstract. Business Engineering emerged as an academic discipline almost a century ago in response to economic demand for experts with both business and engineering expertise. The discipline has since evolved to meet the needs of the fast changing global marketplace. The impact of globalization on the architecture, governance and running of organizations has also shaped the field today. Education has responded to these changes by adapting its architecture and governance to fit international needs. This study examines the case of ESB Business School, Reutlingen University as an example of how business engineering education has been forced to adapt its architecture and governance to fit international needs in the field. Close collaboration with global academic and corporate partners has enabled the school to integrate multiple international components into its business engineering curricula. However, the overall goal remains to ensure that the business engineering education provided is aligned with the global requirements coming from industry. This exploratory industry-driven study tackles this challenge. Qualitative interviews with company representatives of international companies as well as a global industry survey were conducted to examine what study programs and what graduate skill-set are most commonly sought after by industry in different regions of the world. Keywords: Business engineering, competence, employability, domain expertise